The tax regime of third sector entities (European journal of volunteering and community-based projects, 2020)
The tax regime of third sector entities has changed over time; benefits and criteria for non-profit organizations have now been changed by Legislative Decree 117/2017, which reorganized the forecasts for voluntary organizations and social promotion associations. The article focuses on the distinction and tax parameters provided for the activities provided by third sector entities. Tax decommercialization provides specific criteria relating to the way in which the activity must be carried out. The flat-rate determination of business income with the flat-rate regime for third sector entities provides for profitability percentages to be kept under control. Voluntary organizations, philanthropic bodies, and social promotion associations have detailed arrangements.